Efektifitas Promosi melalui Instagram dan Facebook terhadap Volume Penjualan - Shoddiq, Muhammad Jagfar (Keizai, 2022)
To find out the development of a business can be seen from the volume of sales, the profit obtained will be even greater by looking at sales. Sales volume can be increased by conducting conventional or online promotions, to save costs incurred in conducting promotions, it can be done through online media, namely Instagram and Facebook applications. The research method used is descriptive quantitative, promotion through Instagram and Facebook has a positive and significant influence on the sales volume of the Summer Spring perfume business, from Chi-Square it can be seen that promotions through the two media have different sales results. Using the ROAS formula, it is known that promoting on Facebook is more effective than promoting on Instagram.